Behavioural disorders in children and adolescents: Definition, clinical contexts, neurobiological profiles and clinical treatments - Giulio Perrotta; Gianfranco Fabiano (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2021)
Starting from the general concept of behaviour disorder, in childhood, preschool and adolescence, in this work the descriptive boundaries of all diagnostic hypotheses are defined, with an orientation for clinical, neurobiological and therapeutic treatment, not leaving out the socio-cultural, educational and family contexts inherent to the growth of the minor. In the last part of the work the reflexive cues are concentrated on the best theories and techniques of approach in the analysed species cases.